Submarine Instability Processes on the Continental Slope Offshore of Campania (Southern Italy) - Gemma Aiello (GeoHazards)
A revision of the submarine instability processes offshore the Campania region is presented herein based on the literature data and Multibeam bathymetric and seismic profiles previously acquired by the CNR ISMAR of Naples (Italy). Among others, the objectives and perspectives of this research include the following: the chrono-stratigraphic framework of the submarine instability events and their correlation with the trigger geological processes, including the seismicity, the volcanism and the tectonic activity; density reversal has not been detected as a control factor; the implementation of technologies and database for the acquisition and the processing of morpho-bathymetric, seismo-stratigraphic and sedimentological data in the submarine slopes of Campania, characterized by submarine gravitational instabilities. Other main tasks include producing thematic geomorphological maps of the submarine slopes associated with instability phenomena. The principles of slope stability have been revised to be independent of the slope height. In submarine slopes mainly composed of sand, the stability depends on the slope inclination angle concerning the horizontal (β), equal or minor to the internal friction angle of loose sand (ϕ). Based on this research, it can be outlined that the submarine instability processes offshore of Campania mainly occur along the flanks of volcanic edifices, both emerged (Ischia) and submerged (Pentapalummo, Nisida, Miseno, Procida Channel), on steep, tectonically-controlled sedimentary slopes, (southern slope of Sorrento Peninsula, slope of the Policastro Gulf), and on ramps with a low gradient that surround wide continental shelves (Gulf of Salerno).